Holy trinity, holy people : the theology of Christian perfecting - Noble, T. A. (Cambridge : James Clarke & Co., 2013)
Teaching on the sanctification of Christians using the difficult word ""perfection"" has been part of Christian spirituality through the centuries. The Church Fathers spoke of it and Augustine of Hippo particularly contributed his penetrating analysis of human motivation in terms of love. Medieval theologians such as Bernard of Clairvaux and Thomas Aquinas developed the tradition and wrote of levels or ""degrees"" of ""perfection"" in love. However, the doctrine has not fared well among Protestants. John Wesley was the one major Protestant leader who tried to blend this ancient tradition of Chr.
B) The Wesleyan Tradition and the Trinityc) The Monotheistic Model: Holiness as Separation; d) The Trinitarian Model:Holiness as a Communion of Love; e) The Church as the Image of the Holy Trinity; Bibliography; Back Cover.
Includes bibliographical references and index.
Online resource; title from PDF title page (ebrary, viewed October 8, 2013).
Master record variable field(s) change: 072
Keywords: Sanctification -- Biblical teaching; Sanctification -- Christianity -- History of doctrines; Holiness; RELIGION -- Christian Theology -- Soteriology; RELIGION / Christian Theology / Systematic; Electronic books